Mobile Phone Apps for Low-Income Participants in a Public Health Nutrition Program for Women, Infants, and Children (WIC): Review and Analysis of Features - Weber, Summer J; Dawson, Daniela; Greene, Haley; Hull, Pamela C (JMIR Publications, 2018)
BackgroundSince 1972, the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) has been proven to improve the health of participating low-income women and children in the United States. Despite positive nutritional outcomes associated with WIC, the program needs updated tools to help future generations. Improving technology in federal nutrition programs is crucial for keeping nutrition resources accessible and easy for low-income families to use. ObjectiveThis review aimed to analyze the main features of publicly available mobile phone apps for WIC participants. MethodsKeyword searches were performed in the app stores for the 2 most commonly used mobile phone operating systems between December 2017 and June 2018. Apps were included if they were relevant to WIC and excluded if the target users were not WIC participants. App features were reviewed and classified according to type and function. User reviews from the app stores were examined, including ratings and categorization of user review comments. ResultsA total of 17 apps met selection criteria. Most apps (n=12) contained features that required verified access available only to WIC participants. Apps features were classified into categories: (1) shopping management (eg, finding and redeeming food benefits), (2) clinic appointment management (eg, appointment reminders and scheduling), (3) informational resources (eg, recipes, general food list, tips about how to use WIC, links to other resources), (4) WIC-required nutrition education modules, and (5) other user input. Positive user reviews indicated that apps with shopping management features were very useful. ConclusionsWIC apps are becoming increasingly prevalent, especially in states that have implemented electronic benefits transfer for WIC. This review offers new contributions to the literature and practice, as practitioners, software developers, and health researchers seek to improve and expand technology in the program.